Calculation and Characteristic Analysis on Different Types of Shock Response Spectrum. (November 2020) - Sun, Wenjuan; Su, Qiaoping; Yuan, Hongli; Liu, Liqin
Abstract: Shock Response Spectrum (SRS) has been proved to be an effective standard tool for analyzing and quantifying shock environment in engineering, which is also the simplest tool for comparing shock severity and potential damage to structures. The calculation formulas of absolute acceleration spectrum, relative displacement spectrum, relative velocity spectrum and pseudo velocity spectrum are given respectively. The responses of different spectrum under typical semi-sinusoidal shock excitation are compared and analyzed, and some enlightening conclusions are obtained.